Development of a rapid fractionation tool for natural organic matter - Piper, Claire (Cranfield University, 2010)
A rapid natural organic matter (NOM) fractionation tool was developed to enable NOM to be classified by hydrophobicity at the water treatment works and in the catchment. This fractionation method uses XAD adsorption resins to remove hydrophobic (HPO) NOM from solution in 6 minutes. A review of fractionation literature identified the need for this tool, as the information provided by onsite UV254 monitors does not identify the seasonal changes in NOM type. This is needed to enhance effluent quality whilst optimising chemical dosage. The rapid tool was used to fractionate model compounds and natural waters, with the fractions produced compared against the traditional column fractionation procedure. Both fractionation tools recognised the hydrophobicity of the model compounds to be tannic acid>1,3 acetonedicarboxylic acid>d-xylose which agreed with their log KOW values. However, the rapid tool isolated a greater proportion of the model compound with intermediate hydrophobicity due to a higher resin concentration than in the traditional method. Both tools identified the same seasonal trend in the hydrophobicity of Butterley Reservoir, but rapid fractionations produced a lower average % HPO fraction (measured as dissolved organic carbon (DOC) removal from the solution). This was investigated by comparing the relationship between DOC and UV254 for control tannic acid solutions and solutions after prolonged mixing with resin. DOC leaching from the resin was confirmed by DOC concentrations of over 9mgC/L when 10mL resin was mixed with 1L ultra pure water for 72 hours. Resin leaching caused the HPO and transphilic (TPH) fractions to be overestimated in column fractionation with back elution but underestimated in rapid fractionation with mass analysis.
Keywords: NOM; XAD fractionation; rapid; adsorption isotherms; model compounds